“I FOLLOW YOU, I BECOME YOU”: THE INFLUENCE OF MICRO VS MEGA INFLUENCERS’ ATTRIBUTES AND FOLLOWER EMOTIONS ON TRANSFER OF EMOTIONAL ATTACHMENT AND PURCHASE INTENTION IN INDONESIA'S BEAUTY INDUSTRY - Azalia Erda, Florean Haya Soraya; Astuti, Rifelly Dewi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
The rapid growth of the beauty industry in Indonesia has emphasized the role of influencers in building emotional attachment that can influence consumers' purchase intention. This study examines the influence of influencer attributes—namely similarity, inspiration, authenticity, attractiveness, and fun personality—on the transfer of emotional attachment and purchase intention, both directly and through the mediation of emotional attachment and envy. This research offers novelty by comparing the effectiveness of micro-influencers and mega-influencers in the context of Indonesia's beauty industry and applies the Integrative Scale of Digital Influence framework to analyze both direct and indirect effects between variables. The data were collected through a survey of 421 respondents, consisting of 209 mega-influencer followers and 212 micro-influencer followers, and analyzed using PLS-SEM and multi-group analysis. The findings indicate that micro-influencers are more effective in fostering emotional closeness and encouraging purchase intention through perceived authenticity, while mega-influencers tend to influence purchase intention more directly through inspirational content. Feelings of envy did not show a significant impact on emotional attachment or purchase intention. These findings emphasize the importance of selecting influencers based on campaign objectives—micro-influencers for building loyalty, and mega-influencers for quickly reaching a broad audience.